SISTEMA DE CONTROL DE UNA SILLA DE RUEDAS ELÉCTRICA POR MEDIO DE COMANDOS DE VOZ - Rodríguez Bueno, Juan David
This project describes the implementation of a control system for an electric wheelchair by means of voice commands for the displacement of people with motor disabilities, who can not move autonomously. In Colombia, the mechanisms that help to supply this need are expensive, that's why the use of new technologies is important, therefore, this system has an adaptation that activates the joystick of the wheelchair by means of connected servomotors to an Arduino Uno board, which receives commands to perform the movement, from a voice recognition board. The tests carried out contemplated an initial phase of explanation of the voice and training commands in which the person mentioned the action "move forward" and saw the movement of the control, later it was positioned in the chair to achieve the displacement of in flat areas of the center of training.